Industrial training report: Perpustakaan Sultan Salahuddin Abdul Aziz Shah / Nur Yulaily Samarudin - Samarudin, Nur Yulaily (Faculty of Information Management, 2018)
The purpose of this documentation is to report all activities conducted by the trainee during Industrial Training for about 5 months at the Perpustakaan Sultan Salahuddin Abdul Aziz Shah, Selangor. This report encompasses the experience in handling daily tasks and undertakes special projects provided by the organization during 5 months industrial training. From this report, it can measure how far the trainer understands and uses what they learn throughout the industry. This report is written in detail and activities are classified into categories to make it clearer and easier to understand.